The role of intrinsic motivation on relationship between inclusive leadership and job crafting - Çelik, Neriman (Technium Social Sciences Journal, 2024)
The purpose of this study is to examine the mediating role of intrinsic motivation on the relationship between inclusive leadership and job crafting. Simple random sampling method was used in the research. 252 employees willing to participate in the survey from 69 different businesses working in Konya Organized Industrial Zone 1 constituted the sample of the research. The survey technique was used as the data collection technique and data were collected by face-to-face interview method. The total of 252 survey was analyzed through the AMOS-22 and SPSS 27.0 program. As a result of the analysis inclusive leadership has a positive effect on job crafting and intrinsic motivation, and intrinsic motivation has a partial mediator effect on the relationship between inclusive leadership and job crafting. This indicates that when the mediator variable is included in the model, the effect of inclusive leadership on job crafting decreases but does not disappear.